Maternal High-Fat Diet Leads to Non-alcoholic Fatty Liver Disease Through Upregulating Hepatic SCD1 Expression in Neonate Rats - Cao, Baige; Liu, Chongxiao; Zhang, Qianren; Dong, Yan (Frontiers in Nutrition, 2020)
Non-alcoholic fatty liver disease (NAFLD) has become the leading cause of liver disease in children, with evidence that the maternal diet and the early life nutritional environment are potential risk for such disease. This study was aimed to investigate the effects of maternal high fat diet (HFD) on the occurrence of NAFLD in rat offspring and the underlying mechanisms. In this study, the incidence of NAFLD was compared in F1 offspring rats between maternal HFD group and standard chow (SC) group. In addition, the expression levels of inflammatory cytokines in the placenta, umbilical cord blood and in the livers of neonate offspring were compared between two groups. HepG2 cells were treated with recombinant IL6 to assess stearoyl-CoA desaturase 1 (SCD1) expression and lipid synthesis in an inflammatory condition. Lipid accumulation was assayed in both SCD1 overexpression and interference HepG2 cells as well as in neonatal rats. Our results showed that HFD exposure before and throughout the pregnancy induced the elevated hepatic TG content of F1 neonates. The levels of inflammatory cytokines in the placenta, umbilical cord blood and the livers of HFD F1 neonates were significantly higher than that of SC group. In addition, rIL6 treatment led to TG accumulation accompanied by the up-regulation of SCD1 in HepG2 cell lines. Over-expression of SCD1 led to the accumulation of TG contents in HepG2 cells, whereas Scd1 knockdown attenuated the effects of rIL6 treatment. Over-expression of SCD1 in F1 neonatal rats led to hepatic lipid accumulation. Our study indicated that maternal HFD led to intrauterine inflammation, which subsequently caused transgenerationally abnormal hepatic lipid metabolism of F1 neonates. This modulation might be mediated by up-regulating of SCD1 expression in hepatic cells.